A expansão da educação superior na UFMA (2010-2014) no contexto do Reuni - Carvalho, Evandicleia Ferreira de (2016)
The present research was carriede out in the scope of the Master Degree Program in Education at the Federal University of Maranhão (Ufma), linked to the State and Educational Management research line. It has as its object: "The expansion of higher education in Ufma (2010-2014) in the contex of the Restructurign and Expansion Program for Federal Universities (Reuni)", confronting the meanings of elitism, massification and/or democratization in this level of education in official texts and the materialization of such policy on a university campus. This process is investigated in the context of the State reform, the globalization of the economy and the rise of neoliberal policies. In order to do so, it focuses on changes in the policies of higer education in the contemporary world, reflecting on the diversification of course modalities and curricular flexibility in a relationship with international organizations documents and agreements, which are conditioning educational reforms of central and peripheral countries. It reflects on the meanings of massification and democratization relates to higher education expansion policies adopted by the worls. It focuses on expansionist initiative created in Brazil, durging Fernando Henrique Cardoso's governments (1995-2002), Luís Inácio Lula da Silva (2003-2010) and Dilma Vana Rousseff's first governmet (2011-2014). It discusses massification and/or democratization of higher education repercussions. It identifies the meanings and contradictions of Reuni, based on legal conceptions and guidelines, as well as on the appropriation of this Program as Ufma. Finally, we analyze the materialization of Reuni in the University's process of interiorization, translated into the development of courses, student's access and permanence at Ufma - Pinheiro Campus. This text is grounded on the theoretical-methodological basis of historical-dialectical materialism and articulates a bibliographic research (scientific text on the subject), document analysis (laws, decrees, meeting guidelines, plans, projects and reports) questionnairies and interviews. As reference, several authors were used, such as Gentili (2009), Dias Sobrinho (2005; 2010), Ristoff (2008; 2014), Sguissardi (2009), Amaral (2011), Cunha (2003), Ferreira (2009, 2012), Lima K. (2007; 2012), Lima, L. M. (2011) and others. The analysis indicates that the expansion of Ufma (2010-2014) reproduced ambiguities in the overall process of higher education reform and the normative thex of Reuni, representing a restrictes prossibility of expanding the access of young people the working class to entrance opportunities. It considers some improvement in infrastructure, human resources and the entrance of different social groups into undergraduate courses, but with the occurrence of expressive student's drop-out rates and low graduating rates.